1974
DOI: 10.2307/1940358
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Decreasing Water Potential on Net CO2 Exchange of Intact Desert Shrubs

Abstract: This study compares the effects of seasonal (in situ) and experimentally—induced drought on three desert shrubs of different growth types. The effect of decreasing water potential on CO2 uptake was used as the response indicating differences in desert adaptation. Larrea divaricata Cav., Encelia farinosa Gray, and Chilopsis linearis Cav. were selected as representing evergreen, drought—deciduous, and winter—deciduous species respectively. Field measurements of water potential and photosynthesis were made simult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
1
1

Year Published

1978
1978
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(64 citation statements)
references
References 21 publications
5
57
1
1
Order By: Relevance
“…They concluded that changes in specific leaf weight were of adaptive value in allowing these shrubs to remain active into drought periods. In a similar manner, Odening et al (18) concluded that during drought increased specific leaf weight was the factor responsible for enhanced water use efficiency. Our estimates of specific leaf mass in this study indicate that all of the increases in specific leaf mass can be attributed to increases in pubescence.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…They concluded that changes in specific leaf weight were of adaptive value in allowing these shrubs to remain active into drought periods. In a similar manner, Odening et al (18) concluded that during drought increased specific leaf weight was the factor responsible for enhanced water use efficiency. Our estimates of specific leaf mass in this study indicate that all of the increases in specific leaf mass can be attributed to increases in pubescence.…”
Section: Resultsmentioning
confidence: 82%
“…The decline in photosynthesis (A)2 with decreasing leaf water potential (A,) is often linear (1,2,7,12,(15)(16)(17)(18)(19). Both stomatal and nonstomatal components are thought to be responsible for the decreased photosynthetic rate, and several investigators (2,3,7,12,20) these studies, there was a decline in the initial slope of the CO2 dependence curve (OA/Oci, often called the carboxylation efficiency) and also a decrease in A at high ci.…”
Section: Abstracimentioning
confidence: 99%
“…No período seco, essas espécies perdem as folhas para evitar a perda excessiva de água (Borchert 1994;Lima & Rodal, 2010;Lima et al 2012). Em contrapartida, espécies sempre verdes mantém as folhas e as trocas gasosas mesmo sob baixos potenciais hídricos, exibindo clara tolerância ao déficit hídrico (Odening et al 1974).…”
Section: Discussionunclassified
“…Gray (brittlebush) is closely associated with seasonal changes of leaf morphology (Cunningham & Strain, 1969;Odening, Strain & Oechel, 1974;Smith & Nobel, 1977, 1978Ehleringer & Mooney, 1978;Ehleringer, 1988). In particular, development of highly reflective leaf pubescence decreases both leaf heat-load and the reliance on transpirational cooling for maintenance of favourable leaf temperatures (Ehleringer & Mooney, 1978).…”
Section: Introductionmentioning
confidence: 99%